Discovery of Web-Building Spiders in Gua Kelam, Perlis State Park, Malaysia - Johan Ariff Mohtar; Khadijah Hanim Abdul Rahman; Saktheswaran Nyanasilan; Nurul Ain Harmiza Abdullah; Fadhilah Mohamad (Tropical Life Sciences Research, 2024)
A cave represents a subterranean ecosystem that harbours a myriad of unique, peculiar, and secluded flora and fauna. These biotas have evolved with a wide range of ecological adaptations that allow them to thrive in harsh environments with limited light. Gua Kelam 1 constitutes part of the Gua Kelam limestone caves system in the Nakawan Range of Perlis State Park, Malaysia. Previous observations indicated that it harbours a plethora of spider species; however, their existence is still elusive as speleobiological studies remain unexplored. Herein, we identified the cavernicolous spiders found in the dark zone areas of Gua Kelam 1 through a complementary approach based on morphology and DNA barcoding. From the morphological analysis, we described three web-building spiders of JTKK2 and JTKK3 groups down to the species-level to belong to Nephilengys malabarensis, and Orsinome vethi except for Pholcus sp. from JTKK4 individuals. The molecular analysis of the cytochrome oxidase-I (COI) genes of JTKK2 and JTKK3 individuals showed that they exhibited a high degree similarity with N. malabarensis (98.3%), and O. vethi (100.0%), respectively except for JTKK4 individuals with only 91.4% homology with P. kuhapimuk. Phylogenetic analysis also generated a congruent tree, in which the identified species are well nested within the family Araneidae, Tetragnathidae, and Pholcidae. By this integral approach, the three spiders were determined as N. malabarensis, O. vethi, and Pholcus sp. These spiders are originally epigean in their habitat but uniquely thrive in Gua Kelam 1.